Pendidikan Etika Berteman: Sebagai Upaya Membentuk Lingkungan Sekolah Bebas Bullying Di SDN PRINGORI - Hurul Aini; Dzaky Ariya Saputra; Muhamad Fajar Ismail; Indah Syafitri; Kayla Rayane Putri; Aulia Suci Ramadhani; Aldiansyah Ramadhan; Rohid Rohid; Siti Najla Destria Aprisari; Wiwit Akmalina (JURNAL ILMIAH NUSANTARA, 2025)
Bullying is one of the problems that often occurs in the school environment and has a negative impact on students' psychological, social and academic development. One of the preventive efforts that can be made is through friendship ethics education that instills moral and social values, such as empathy, tolerance, mutual respect, and avoiding behavior that harms others. This research uses the literature study method by reviewing various relevant sources, including books, scientific journals, and educational policies related to bullying prevention. The results show that friendship ethics education plays an important role in shaping the character of students who are able to interact positively with peers, reduce the potential for bullying, and create a safe and harmonious school environment. The successful implementation of friendship ethics education is strongly influenced by integration in the curriculum, habituation in school culture, exemplary teachers, and parental involvement. With consistent implementation, befriending ethics education can be an important foundation in creating bullying-free schools.